Face-to-face information combined with a booklet versus a booklet alone for treatment of mild low-back pain: a randomized controlled trial - Jarmo Rantonen; Aki Vehtari; Jaro Karppinen; Satu Luoto; Eira Viikari-Juntura; Markku Hupli; Antti Malmivaara; Simo Taimela (Nordic Association of Occupational Safety and Health (NOROSH), 2014)
OBJECTIVE: The aim of this study was to determine the effectiveness of face-to-face information for the treatment of mild low-back pain (LBP) in an occupational health (OH) setting. METHODS: We conducted a 48-month randomized controlled trial (RCT) with two 1:1 allocated parallel groups of forestry company employees. Eligibility criteria included permanent employment, age <57 years, and mild LBP [visual analogue scale (VAS) 10-34 mm] in a survey. The intervention group received the Back Book, an information booklet on how to manage LBP, with an additional face-to-face review of the booklet by an OH nurse. The control group received the booklet only. Primary outcomes were physical impairment (Roland-Morris 18-item (RM-18) Disability Questionnaire), LBP (VAS 100 mm), health-related quality of life [15-dimensional quality of life (15-D)] during two years and sickness absence (SA) up to four years. Participants were assigned using block randomization with a computer-generated scheme. RESULTS: The RCT comprised 181 participants (72% male, mean age 44 years). There were no differences between the treatment arms in any of the primary outcomes at any time point. At 24 months, the mean group differences (intervention versus control) were: RM-18: 0 [95% confidence interval (95% CI) -1-1], VAS: 3 mm (95% CI -3-8), and 15-D 0.00 (95% CI -0.02-0.02). The difference in cumulative sickness absence days at 48 months were -3 (95% CI -28-21) for total and 1 (95% CI -3-5) for LBP specific sick leaves. Exploratory analysis revealed no differences at subgroup-levels either. CONCLUSIONS: Face-to-face patient information by an OH nurse in addition to a booklet was not more effective than the booklet alone in treating employees with mild LBP in an OH setting.